NYERI DISMENOREA PADA REMAJA PUTRI DI SMPN 11 MATARAM TAHUN 2015 - Murtiana Ningsih (SANGKAREANG, 2016)
Dismenorrea is abdominal pain derived from uterine camps and happened during menstruation. Giving of warm compresses is one of non pharmacology therapy to dismenorrea pain. This study was aimed to know the relationship between using warm compresses and changes of dismenorrea pain level on teenage girl at SMPN 11 Mataram in 2015. This study is experimental study by true experiment pretest-post-test control group. Population if the study is teenage girl at SMPN 11 Mataram in 2015 in the amount of 379 students. Number of samples in the amount of 62 student by accidental sampling technique. Data are taken by observation on respondent. Data are analyzed by coefficient contingency correlation test and logistic regression test then analyzed different of probability value and determination coefficient value between the two test instruments so that got proper test instrument ti analyze nominal scale data. Based on the result of statistical test by coefficient contingency got p value = 0,002 whereas by logistic regression test got p value = 0,001. It showed there was significant relationship between using warm compresses and changes of dismenorrea pain level on teenage girl at SMPN 11 Mataram in 2015. Besides, it is found different determination coefficient between each instrument test in which coefficient contingency r 2 = 0,1369 and logistic regression r 2 = 0,224. It can be concluded that both of the test instruments probability value to reject H 0 < 0.05 whereas its determination coefficientvalue is different on each test instruments. Effort to give counseling to teenage girl is necessary to prevent dismenorea and warm compresses can be used as one of the prevention efforts.